Diy laboratories, their practices, and challenges – a systematic literature review. Issue 10 (3rd October 2021) - Dzandu, Michael D.; Pathak, Buddhi
ABSTRACT: The last two decades have seen a growing literature worldwide on do-it-yourself (DiY) laboratories driving informal innovation. However, there is a limited account of the state-of-the-art DiY literature to the emergence of DiY laboratories or of the challenges, strategies for its diffusion and success. This study, therefore, aims to understand the state-of-the-art of DiY laboratories. Using the systematic literature review approach, 29 articles are analysed. The results revealed that the main purpose of publications on DiY laboratories was geared towards showcasing informal innovation. Most of the studies used the case study methodology and most were underpinned by theories from innovation literature. The success factors identified for DiY laboratories include personal motivation and the desire to create a business, whilst their emergence was driven by the need for extra income, experimenting with new ideas and the pursuit of hobbies outside formal work settings. Key challenges faced by DiY laboratories include economic and marketing factors, especially access to finance to scale up their innovations. The strategies used by DiY laboratories to diffuse their innovations are social networking, partnerships with bigger tech firms and selling off their innovations to investors. The study outlines the implications for practitioners, entrepreneurs, and government, and makes recommendations.